TO COMPARE THE METABOLIC SYNDROME AND ITS ASSOCIATED FACTORS WITH THE NORMAL HEALTHY POPULATION - KAUR, INDERPREET; JINDAL, PURNIMA; AHI, RAJINDERJIT SINGH; KAUR, JASWANT (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Metabolic syndrome (MetS) is an associated conditions that together rise the risk of cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). The study’s hypothesis was to assess the prevalence of the Mets and its associated factors among the North Indian population. Methods: The prevalence of the MetS was estimated to be two hundred patients who visited the hospital of Guru Nanak Dev, Sri Amritsar. Following variables such as body mass index, waist circumference, high-density lipoprotein-cholesterol, triglycerides, and fasting blood glucose were done. Results: The prospective observational study revealed that the prevalence of the MetS was higher in women than men, based on the International Diabetes Federation definition (female-55% and male-45%). MetS was more prevalent in the study of patients with age >60 years. A strong association was found between the above parameters (p<0.05) with the Mets. Conclusion: Amid the Mets driving the twin global pandemic of CVD and T2DM. There is a medical and economic imperative to identify those individuals with the Mets, so that interventions and treatment may prevent T2DM with CVD.